IEEE 802.1 AVB and its application in carrier-grade ethernet. - Garner, Geoffrey M. (IEEE Communications magazine)
Ethernet is increasingly being used in carrier networks to transport real-time traffic, including wireless backhaul network traffic, time-sensitive audio/video applications in access networks, and circuit emulation for legacy services. With the replacement of traditional circuit-switched networks with Ethernet-based packet networks, it must be ensured that the application timing and QoS requirements are met. The IEEE 802.1 Audio/Video Bridging Task Group is developing a comprehensive set of standards to enable high quality, low-latency streaming of time-sensitive applications. These standards specify a means of providing time synchronization (IEEE 802.IAS), a resource reservation protocol (IEEE 802.1Qat), and a set of forwarding and queuing rules that bound the variability of delay in an AVB network (IEEE 802.1Qav). These standards are described, including their potential application to carrier-grade Ethernet networks.